Development of three-dimensional profiled woven fabrics on narrow fabric looms. Issue 12 (July 2016) - Fazeli, Monireh; Kern, Martin; Hoffmann, Gerald; Cherif, Chokri
Three-dimensional (3D) profiled woven fabrics with varying cross-sections along the component parts are needed in a number of industrial applications. One of the main advantages of the ribbon loom weaving technique is the ability to produce highly diverse structures with open or closed edges. The realization of 3D profiled woven fabrics that satisfy the requirements is directly connected to the ability to process high-performance fibers in the weft direction. The processing of high-performance yarns in the weft direction with low fiber damage will open new application areas for shuttle weaving machines. By employing modified mechanical loom elements, the variety of producible structures can be increased significantly.